Prevalence, Economic Contribution, and Determinants of Trees on Farms across Sub-Saharan Africa - Miller, Daniel C. (Elsevier, 2018)
Trees on farms are often overlooked in agricultural and natural resource research and policy in Sub-Saharan Africa. This article addresses this gap using data from the Living Standards Measurement Study-Integrated Surveys on Agriculture in five countries: Ethiopia, Malawi, Nigeria, Tanzania, and Uganda. Trees on farms are widespread. On average, almost a third of rural smallholders grow trees. They account for an average of 17% of total annual gross income for tree-growing households and 6% for all rural households. Gender, land and labor endowments, and especially forest proximity and national context are key determinants of on-farm tree adoption and management. These new, national-scale insights on the prevalence, economic contribution and determinants of trees on farms in Africa lay the basis for exploring the interaction of agriculture, on-farm tree cultivation, and forestry to gain a more complete picture of the dynamics of rural livelihoods across the continent and beyond.